ANALISIS MANAJEMEN TERHADAP KESIAPAN PENERAPAN REKAM MEDIS ELEKTRONIK DI RUMAH SAKIT ERIA - Yuliana, Anastasya Shinta; Lubis, Sylvi Chairuniza; Firdaus, Muhammad; Tonis, Marian (LPPM Universitas Awal Bros, 2024)
Electronic Medical Record (EMR) or Electronic Medical Record (RME) is a form of medical record system that uses electronics based on sheets of paper or medical record files. The application of Electronic Medical Record (EMR) requires readiness analysis, which is one way to explore the potential causes of the failure of an innovation. Therefore, it is necessary to carry out readiness assessment activities prior to implementing RME. This research is a type of qualitative research with an analytic descriptive approach with a total of 5 informants, which was carried out on February 8 - August 5, 2023. The methods used were in-depth interviews, observation and document review. The results of the study found that in the man variable, the Eria Hospital medical record unit did not have work shifts and staff were not involved in the preparation process EMR. The money variable Overall budget preparationEMR Not yet budgeted, but can be held as needed. The materials variable Eria Hospital already has an internet connection and that allows for EMR. The methods variable strategic planning in preparationEMR already exists and currently uses a manual medical record flow. The machine variable there is an assessment of hardware requirements, desktop terminals and other devices needed to support the use of electronic medical records. It is recommended that there should be additional medical record officers and special training regardingEMR, adding machines/facilities such as adding laptops/computers and printers to make them effective, and need to display SOPs in the medical records room